Osteoid osteoma of the mandible: case report - Cury, Sergio Elias Vieira; Silva, Brunno Santos de Freitas; Rocha, André Caroli; Lemos-Junior, Celso Augusto; Junior, Décio dos Santos Pinto (Journal of Oral Diagnosis, 2016)
We present a rare case of a 39-year-old woman who had a painless mass in the mandibular symphysis. Histological findings showed a benign osteoid osteoma.